Gerakan Literasi Islamiyah melalui Program Dakwah dan Tarbiyah di Desa Mangeloreng Kabupaten Maros - Istikhariyah Muin; M. Amirullah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
One form of community service for the STIBA Makassar KKN students in Baruga Village, Bantimurung District, Maros Regency is to carry out the Da'wah and Tarbiyah programs. The aim of this program is to increase the understanding and competence of Islamic communities in Baruga Village. The details of the Da'wah and Tarbiyah programs are: 1) Dirosa activities; 2) Tahsin activities; 3) Muslim Muslim women; 4) Tausiyah Qur'aniyah; 5) Teaching PAI; 6) Development of TKA / TPA; 7) Training for Organizing the Body. The output of the da'wah and tarbiyah programs made a positive contribution to increasing Islamic understanding of residents in Baruga Village.One form of community service for the STIBA Makassar KKN students in Baruga Village, Bantimurung District, Maros Regency is to carry out the Da'wah and Tarbiyah programs. The aim of this program is to increase the understanding and competence of Islamic communities in Baruga Village. The details of the Da'wah and Tarbiyah programs are: 1) Dirosa activities; 2) Tahsin activities; 3) Muslim Muslim women; 4) Tausiyah Qur'aniyah; 5) Teaching PAI; 6) Development of TKA / TPA; 7) Training for Organizing the Body. The output of the da'wah and tarbiyah programs made a positive contribution to increasing Islamic understanding of residents in Baruga Village.